Canadian National Guidelines and Recommendations for Integrating Career Advising Into Medical School Curricula. (November 2017) - Howse, Kelly; Harris, June; Dalgarno, Nancy
Abstract : Career planning, decision making about specialty choice, and preparation for residency matching are significant sources of stress for medical students. Attempts have been made to structure and formalize career advising by including it in accreditation standards. There is an expressed need for national guidelines on career advising for medical students. The Future of Medical Education in Canada Postgraduate (FMEC PG) Implementation Project was created to ensure Canadian medical trainees receive the best education possible. From this, a diverse sub-working group (SWG), representing different Canadian regions, was formed to review career advising processes across the country. The SWG developed, through a modified formal consensus methodology, a strategy for medical student career advising that is adaptable to all schools in alignment with existing accreditation standards. The SWG outlined five guiding principles and five essential elements for Canadian universities offering an MD degree with recommendations on how to integrate the elements into each school's career advising system. The five essential elements are a structured approach to career advising, information about available career options, elective guidance, preparation for residency applications, and social accountability. This Perspective endorses the view of the FMEC PG Implementation Project that national guidelines are important to ensure Canadian medical schools are consistently meeting accreditation standards by providing reliable and quality career advising to all medical students. The SWG's position, based on national and provincial feedback, is that these guidelines will stimulate discourse and action regarding the requirements and processes to carry out these recommendations nationwide and share across borders.